2022
DOI: 10.1088/1742-6596/2376/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivity Enhancement of TiO2 Nanoparticle-decorated ZnO as a Photocatalyst in Methylene Blue Degradation

Abstract: Zinc Oxide (ZnO) and Titanium Dioxide (TiO2) are metal oxides that are commonly used as photocatalysts material due to photoactivity characteristics. ZnO has a better reduction potential, and high electron mobility, but has a lower contact surface area than TiO2. On the other side, TiO2 has a better photoactivity to degrade pollutants referring to high surface area but has lower electron mobility compared to that ZnO. The combination of these two metal oxides is estimated can produce a better photocatalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In our previous result, the ZnO particles formed possessed spherical shape and size were less than 50 nm [7]. Figure 3 shows the morphology of the ZnO films.…”
Section: Sem/eds Ca Studiesmentioning
confidence: 68%
See 3 more Smart Citations
“…In our previous result, the ZnO particles formed possessed spherical shape and size were less than 50 nm [7]. Figure 3 shows the morphology of the ZnO films.…”
Section: Sem/eds Ca Studiesmentioning
confidence: 68%
“…The spraying deposition technique (applying temperature treatment) and the gel concentration do not affect crystal structure, such as crystallite size, FWHM, and lattice constants. The photocatalytic activity is slightly affected by surface morphology, (7) 14th International Symposium on Modern Optics and Its Applications Journal of Physics: Conference Series 2696 (2024) 012009…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that functionalized ZnO and TiO2 mainly produce •OH and O2 •‾ , which act together in the degradation process [53,54]. In general, SPION@SiO2@ZnO and SPION@SiO2@TiO2 are very similar; however, the difference in their degradation rate stems from the fact that SPION@SiO2@TiO2 has a higher surface area, which improves the ability to harvest incident light and create more surface-active sites [55].…”
Section: Kinetic Studymentioning
confidence: 99%